MANAJEMEN MUTU INTERNAL DALAM MEMBANGUN SATUAN PENDIDIKAN RAMAH ANAK DI RA PERWANIDA - Rohmah, Indah Inayah; Isnaeni I, Wiwin Yuni; Happyana, Lu’at; Dausat, Muhammad Jangki (Hijri, 2024)
This study focuses on internal quality management efforts in creating a child-friendly educational environment at RA Perwanida 1 Pesanggaran, Banyuwangi. The background of this research is based on the need to improve educational quality through enhancements in managerial aspects, including planning, implementation, and evaluation. The aim of the study is to establish an educational environment that is safe, comfortable, and supports children's holistic development. Using a qualitative case study approach, the research delves into the school's efforts to implement child-friendly principles through internal quality management strategies. Primary data were collected through in-depth interviews with the principal, teachers, staff, and parent representatives, while supporting data were obtained from policy documents and school evaluation reports. To ensure data validity, source and method triangulation techniques were employed. The study identifies five main strategies implemented by RA Perwanida: strengthening internal policies to establish a transparent system, prioritizing anti-bullying education to build children's character, enhancing the quality of a safe and comfortable learning environment, developing a child rights-based curriculum, and encouraging active participation from parents and the community. These strategies have proven effective in supporting the establishment of a child-friendly educational institution. The research concludes that the success of building a child-friendly school heavily relies on well-planned and integrated internal quality management. The implications of this study highlight the importance of systematic data-based evaluations and active collaboration between schools, parents, and communities to ensure program sustainability. Empirically, this study provides a significant contribution to the development of child-friendly education models, particularly in early childhood education settings.